Quantum Chemical (QC) Calculations and Linear Solvation Energy Relationships (LSER): Hydrogen-Bonding Calculations with New QC-LSER Molecular Descriptors - Costas Panayiotou (Liquids)
A new method, based on quantum chemical calculations, is proposed for the thermodynamically consistent reformulation of QSPR-type Linear Free-Energy Relationship (LFER) models. This reformulation permits the extraction of valuable information on intermolecular interactions and its transfer in other LFER-type models, in acidity/basicity scales, or even in equation-of-state models. New molecular descriptors of electrostatic interactions are derived from the distribution of molecular surface charges obtained from COSMO-type quantum chemical calculations. The widely used and very successful Abraham’s Linear Solvation Energy Relationship (LSER) model is selected as the reference LSER model for the calculations in solute–solvent systems as well as in solute self-solvation. Hydrogen-bonding free energies, enthalpies, and entropies are now derived for a variety of common solutes. The capacity of the method to address the role of conformational changes in solvation quantities is discussed. The perspectives of the LSER model with the implementation of the new descriptors are also discussed.